THE INFLUENCE OF PROFITABILITY, LIQUIDITY, AND LEVERAGE ON THE FIRM VALUE OF MANUFACTURING COMPANIES IN THE COAL MINING SUBSECTOR LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) DURING THE 2021–2024 PERIOD - INTAN NUR'AINI; Anzani Mutiara Puwitasari; Aisyah Diah Hapsari (Kampus 5 Universitas Negeri Surabaya, 2025)
This study aims to examine the influence of profitability, liquidity, and leverage on firm value in coal mining manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Profitability is measured using Return on Equity (ROE), liquidity is measured using the Current Ratio (CR), leverage is measured using the Debt to Equity Ratio (DER), and firm value is measured using Price to Book Value (PBV). This research employs a quantitative method with an inferential statistical approach. The study population consists of twenty-two coal mining companies listed on the IDX between 2021 and 2024, from which six companies were selected using purposive sampling based on specific research criteria. The study uses secondary data obtained from annual and audited financial reports published on the official IDX website. Data analysis techniques include descriptive statistical analysis, classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity), and hypothesis testing through multiple linear regression analysis using the t-test and F-test with SPSS version 25. The findings of this study are expected to provide insights into the financial factors influencing firm value in Indonesia’s coal mining subsector. Keywords: Profitability, Liquidity, Leverage, Firm Value, Coal Mining, Indonesia Stock Exchange.